Field verification of the surface renewal method for evapotranspiration measurement in arid agricultural area: The uncertainty of calibration parameter - Zhen Wang; Nanjuan Zheng; Bingbing Jiang; Yao Rong; Xin Li; Peijin Wu; Weishu Wang; Chenglong Zhang; Zailin Huo (Journal of Hydrology, 2025)

Anti-interference detection of Pb (II) in seawater enabled by a photo-electrostatic ZnFe2O4/MoS2 heterojunction electrode - Shu Huo; Rong Guo; Gengchen Li; Hong Liu; Wenbo Hang; Tingting Liu; Ye Ma; Minggang Zhao (Chemical Engineering Journal, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Molecular Insight Into the Hydrolysis of Phthalate Esters by a Family IV Esterase - Zhen Rong; Li‐Guo Hong; Ying‐Yi Huo; Jixi Li; Dao‐Qiong Zheng; Yang Ha; Jeffrey Fan; Xue‐Wei Xu; Yue‐Hong Wu (Environmental Microbiology, 2025)
Phthalate esters (PAEs) are prevalent environmental contaminants, with their biodegradation efficiently driven by microorganisms through ester bond hydrolysis. This study investigates the mechanism of Poc14, a novel family IV esterase, using x‐ray crystallography, bioinformatics, biochemistry and site‐directed mutagenesis. Phylogenetic analysis classifies Poc14 as a family IV esterase with conserved catalytic motifs crucial for its activity. Poc14 retains over 80% activity at 50°C for 4 h and tolerates up to 5% methanol or DMF, though surfactants like Tweens inhibit its function. Poc14 activity is independent of metal ions, and the addition of EDTA further enhances its activity by approximately 130%. The 1.8 Å crystal structure reveals a CAP domain and two substrate channels. Enzyme assays show Poc14 hydrolyses short‐chain diethyl phthalate (DEP) ( K m = 0.068 mM, V max = 9975 μM/min/mg) but not long‐chain di(2‐ethylhexyl) phthalate (DEHP) due to steric hindrance. Molecular docking assessed Poc14's potential to hydrolyse DEP and DEHP after residue mutations, resulting in the Poc14‐AAG variant. Poc14‐AAG could hydrolyse one bond of DEHP and diester bonds of DEP. Our study positions Poc14 as a promising enzyme for environmental remediation, with potential for optimising DEHP degradation and exploring dimerisation effects.

Multi-stage dolomitization controlled by sedimentary facies and basement faults: Insights from the Middle Permian Maokou Formation of the Eastern Sichuan Basin, SW China - Rong Yang; Xiyan Yang; Yang Li; Cunhui Fan; Yue Li; Zisang Huang; Fei Huo; Xingzhi Wang; Xiangyu Fan (Marine and Petroleum Geology, 2025)

A millennial record of lake ecosystem responses to climatic variability in the Yellow River Source Area - Jianan Zheng; Rong Wang; Hanxiao Zhang; Shouliang Huo; Jingjing Li; Yanjie Zhao; Ji Shen (Quaternary Science Reviews, 2025)

The efficacy, safety, and persistence of vedolizumab versus adalimumab in patients with inflammatory bowel disease: a systematic review and meta-analysis - Zhixin Chen; Huo Li; Zhongzhuan Li; Rong Ouyang; Shijiang Huang; Shufen Qin; Jing Qin; Jiean Huang (Inflammopharmacology, 2025)

Machine learning discovery of novel antihypertensive peptides from highland barley protein inhibiting angiotensin I-converting enzyme (ACE) - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Yiqing Zhu; Mengyao Huo; Rong Li; Yichen Hu; Qun Shen; Yong Xue (Food Research International, 2025)